STRATEGI PEMASARAN MEDIA SOSIAL UNTUK PERGURUAN TINGGI ISLAM: MENINGKATKAN KETERLIBATAN MEREK DI ERA DIGITAL - Muhammad Kholilurrohman; Muhammad Thoiful Abrar; Ida Kusumawati; Unzilah Khomairohtus Shiyamah; Siti Khofsah; Zackyl Musthofa; Badrul Mudarris (Jurnal Manajemen Pendidikan, 2026)
The growth of social media has encouraged universities to utilize it as a digital marketing tool to increase audience engagement. This study aims to analyze social media marketing strategies for enhancing brand engagement at Islamic universities, specifically at STAI Al-Utsmani, Jambesari Darus Sholah, Bondowoso. The method used is a qualitative approach employing a case study and grounded research. Data collection was conducted through observation, in-depth interviews, questionnaires, and a desk review of documents and social media content. Data analysis was conducted through the stages of data condensation, data presentation, and verification, using content analysis, discourse analysis, and interpretive analysis techniques. The research results indicate that the dominance of informative content and low levels of digital interaction are the primary factors hindering audience engagement, while the integration of Islamic values has been shown to hold potential in enhancing emotional engagement. It is concluded that the success of social media marketing is not only determined by the intensity of posts but also by content quality, interactivity levels, and the relevance of the values conveyed. The implications of this study underscore the importance of transforming social media marketing strategies through the development of more interactive, creative, and Islamic-value-based content to sustainably enhance brand engagement.